Pengaruh Motivasi dan Disiplin Kerja terhadap Kinerja Karyawan pada PT PLN (PERSERO) UPDL Tuntungan, Medan - M. Risky Kudadiri; Safaruddin Safaruddin; Desri Wiana; Dewi Comala Sari; Sarah Rouli Tambunan (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2024)
Employee performance is the result of work given to the company as a form of contribution from each employee in the process of achieving company goals both in the short and long term. In order for employees to work with high productivity, effective, efficient, and targeted motivation and work discipline are needed so that they will produce positive performance so that employee work performance increases. This study aims to determine the effect of motivation and work discipline on employee performance. The research method used is a quantitative method and the research location is at PT PLN (Persero) UPDL Tuntungan, Medan. The population in this study were employees working at PT PLN (Persero) UPDL Tuntungan, Medan, totaling 58 people and all of them were sampled using a sampling technique, namely the Sensu/Saturated Sampling technique. Data collection techniques used include interviews, observations and questionnaires. The data analysis method in this study is validity testing, reliability testing, classical assumption testing, multiple linear regression and hypothesis testing. The data processing technique uses IBM SPSS 27 Statistics. Based on the results of partial research from the two independent variables that most influence employee performance is the work motivation variable. Simultaneously explains that motivation and work discipline have a positive and significant influence on employee performance at PT PLN (Persero) UPDL Tuntungan, Medan. The results of the determination test show that motivation and work discipline have an influence on employee performance at PT PLN (Persero) UPDL Tuntungan, Medan by 65.6% and the remaining 34.4% is influenced by other factors outside the research.